2020
DOI: 10.1108/bfj-06-2019-0429
|View full text |Cite
|
Sign up to set email alerts
|

Is craft beer consumption genderless? Exploratory evidence from Italy and Germany

Abstract: PurposeThis study aimed to investigate the gendered nature of craft beer (CB) consumption in Italy and Germany.Design/methodology/approachData were collected through online surveys in Italy (N = 210) and Germany (N = 211). Based on an enhanced version of the theory of planned behaviour, mean value difference tests and moderated regression analyses with gender as a moderator were performed to test gender effects on CB consumption behaviour.FindingsThe study results provide evidence that the gap in CB consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…They perceive CB as having a higher quality, more flavors than commercial beer, thus tastier, more genuine and natural. Using both Italian a German samples Rivaroli et al (2020) identified only moderate gender effects in attitudes toward CB consumption for Italians and no significant effects for Germans; therefore, they concluded that CB consumption is genderless.…”
Section: Analysis Of the Resultsmentioning
confidence: 93%
“…They perceive CB as having a higher quality, more flavors than commercial beer, thus tastier, more genuine and natural. Using both Italian a German samples Rivaroli et al (2020) identified only moderate gender effects in attitudes toward CB consumption for Italians and no significant effects for Germans; therefore, they concluded that CB consumption is genderless.…”
Section: Analysis Of the Resultsmentioning
confidence: 93%
“…Hal ini memperkuat penelitian sebelumnya bahwa peran moderasi gender bermakna pada pengaruh minat beriwirausaha (Setyawan, 2016). Dalam studi eksploratif konsumsi beer di Jerman gender tidak dapat memoderasi efek dari komponen model pada niat perilaku, sedangkan di Italia gender memoderasi perceive behavior dengan menggunakan Theory Planned Behaviour (Rivaroli et al, 2020). Sehingga perbedaan gender dalam merancang strategi untuk meningkatkan mengkonsumsi makanan tradisional, perlu mempertimbangkan cara individu dalam menilai dan merespon faktor-faktor tersebut untuk meningkatkan pengambilan keputusan dalam pemilihan makanan.…”
Section: Pembahasanunclassified
“…This is reflected in the shift from a mass and industrial approach to a slower one, in line with the Slow Food philosophy (Garavaglia, 2015), aimed at learning in tasting and the pleasure of savouring different and new flavours (Schnell and Reese, 2009;Fastigi et al, 2015a;Donadini and Porretta, 2017;Garavaglia, 2015). The behaviour and habits of beer consumers are the subjects of numerous studies (Donadini and Porretta, 2017;Lerro et al, 2020;Carbone and Quici, 2020;Massaglia et al, 2022;Merlino et al, 2020;Pilone et al 2023;Rivaroli et al, 2019;Rivaroli et al, 2020) aimed at defining craft beer marketing and promotion strategies. One of the relevant elements for consumers is authenticity, understood as a guarantee of product quality, service quality, transparency and traceability (Hernandez-Fernandez and Lewis, 2019;Verhaal and Dobrev, 2022).…”
Section: Introductionmentioning
confidence: 99%